OsBGLU19 and OsBGLU23 regulate disease resistance to bacterial leaf streak in rice - Bei-bei LI; Ying-gao LIU; Tao WU; Ji-peng WANG; Gui-rong XIE; Zhao-hui CHU; Xin-hua DING (Journal of Integrative Agriculture)
β-Glucosidase belongs to the glycoside hydrolase I family, which is widely present in multiple species and responds to various biotic and abiotic stresses. In rice, whether β-glucosidase is involved in the interaction between plants and microorganisms is not clear. In this study, we found that the expression of several genes encoding β-glucosidases, including OsBGLU19 and OsBGLU23, were upregulated after inoculation with Xanthomonas oryzae pv. oryzicola (Xoc) and downregulated after inoculation with X. oryzae pv. oryzae (Xoo). The respective insertion mutants of OsBGLU19 and OsBGLU23, bglu19 and bglu23, were more susceptible to Xoc infection. The expression of OsAOS2, a key gene in the jasmonic acid signal pathway, was dramatically downregulated after inoculation with Xoc in the bglu19 and bglu23 mutants. Simultaneously, the expression of downstream disease resistance-related genes, such as OsPR1a, OsPR5 and a key transcription factors OsWRKY72 were obviously downregulated. The resistance mediated by OsBGLU19 and OsBGLU23 to bacterial leaf streak is related to disease resistance-related genes above mentioned.